Investigation of the antimycobacterial activity of fungal endophytes and their magnetic dendrimer stabilized nanoparticles against mycobacteria - Hussan, Raeesa Hoosen (Stellenbosch : Stellenbosch University, 2024)
Thesis (PhD)--Stellenbosch University, 2024.